Maternal exposure to ambient PM2.5 exaggerates fetal cardiovascular maldevelopment induced by homocysteine in rats. Issue 3 (20th May 2016) - Chen, Huiqing; Chen, Xiaoqiu; Hong, Xinru; Liu, Chaobin; Huang, Huijuan; Wang, Qing; Chen, Suqing; Chen, Hanqiang; Yang, Kai; Sun, Qinghua
ABSTRACT: Maternal exposure to airborne particulate matter with aerodynamic diameter <2.5 µm (PM2.5 ) during pregnancy and lactation periods is associated with filial congenital cardiovascular diseases. This study aimed to investigate the toxic effects of maternal exposure to ambient levels of PM2.5 on filial cardiovascular maldevelopment induced by homocysteine. Using a 2 × 2 factorial design, rats were randomized into four groups and were exposed to ambient PM2.5 or filtered air (FA) throughout the pregnancy and lactation periods coupled with the administration of either homocysteine (HCY) or normal saline (NS) daily from gestation days 8–10. Morphological changes in the heart, myocardial apoptosis, expressions of cardiac progenitor transcriptional factors, and levels of cytokines were investigated in the offspring. The apoptosis‐like changes in the myocardium were seen in the FA plus HCY‐treated group and more obviously in the PM2.5 plus HCY‐treated group, which was in accordance with an increased myocardial apoptosis rate in the two groups. PM2.5 exposure resulted in significantly decreased Nkx2‐5 protein level and GATA4 and Nkx2‐5 mRNA expressions, and significantly increased TNF‐α and IL‐1β levels. There were significant interactions between PM2.5 exposure and HCY‐treatment that PM2.5 exposure reduced Nkx2‐5 protein levels and GATA4 and Nkx2‐5 mRNA expressions in the HCY‐treated groups. These results suggest that maternal exposure to PM2.5, even at the ambient levels in urban regions in China, exaggerates filial cardiovascular maldevelopment induced by HCY in a murine model, exacerbating structural abnormalities in the filial cardiac tissue, which is possibly associated with oxidative stress and reduced GATA4 and Nkx2‐5 transcription factor expressions. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 877–889, 2017.